As formas [V+do] em português: um estudo de classes e palavras - Bueno, Mariza do N. S. Pimenta (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
This paper, which is part of a more extensive work aiming at the establishment of objective criteria for characterizing word-classes in Portuguese, studies Portuguese [V+do] forms and claims that these forms do not constitute a lexically uniform group. It shows that, in addition to having [V+do] forms with are clearly verbal and [V+do] forms which are unequivocally adjectival, Portuguese has [V+do] forms whose lexical characterization is somewhat problematic, in so far as they have both adjectivak and verbal syntactic properties, but are not thoroughly identifiable either with the class of verbs or with that of adjectives. The paper proposes thet the latter group of [V+do] forms, which derive from directly transitive verbal bases, be categorized as passive participles (PP's), a third class, The lexical solution proposed is able to account for constructions with ser (...) [V+do] which allow both a stative (Adj) and a "passive-eventive" (PP) reading for the [V+do] forms.